Synthesis of self-modified black BaTiO3−x nanoparticles and effect of oxygen vacancy for the expansion of piezocatalytic application. (May 2022) - Ji, Myeongjun; Kim, Jeong Hyun; Ryu, Cheol-Hui; Lee, Young-In
Abstract: Piezocatalysis is considered as a promising green and sustainable technology because of its ability to promote passive conversion of natural mechanical energy into electrochemical energy. Barium titanate (BaTiO3 ) nanoparticles have been actively studied as a piezocatalyst because of their non-toxicity, physicochemical stability, and high piezoelectric potential. However, their low carrier concentration is a significant drawback that limits their applicability as piezocatalysts only in ultrasonic systems, which can thermally excite BaTiO3 via cavitation. The defect engineering is a useful technique to modulate the electrical property of materials via a simple process involving the introduction of atomic defects. However, only a few reports on the synthesis of black BaTiO3−x are available, and investigations on the piezocatalytic performance of black BaTiO3−x nanoparticles have not yet been reported. In this study, the self-modified black BaTiO3−x nanoparticles were successfully synthesized through a simple solid-state reaction using defective raw materials in the reducing atmosphere. The effect of oxygen vacancies in the raw materials on the synthesis mechanism, size, and defect concentration of the final products was effectively demonstrated. Furthermore, the efficiency of defect engineering in improving the piezocatalytic performance in terms of free carrier concentration was systematically studied and subsequently proved. This paper reports a pioneering strategy that can promote the widespread practical applications of black BaTiO3−x as a piezocatalyst. Graphical Abstract: ga1 Highlights: The self-modified black BaTiO3−x nanoparticle was successfully synthesized by a facile solid-state route. The electron concentration of BaTiO3−x was dramatically increased compared to its white form by oxygen vacancies. Black BaTiO3−x exhibit a slightly improved piezocatalytic property under ultrasonic than white BaTiO3 despite the defects. The low energy-harvesting performance of black BaTiO3−x was demonstrated by piezocatalytic degradation under sirring system.